The Covid-19 Learning Crisis as a Challenge and an Opportunity for Schools: An Evidence Review and Conceptual Synthesis of Research-Based Tools for Sustainable Change - Riikka Hofmann; Gabrielle Arenge; Siobhan Dickens; Javiera Marfan; Mairead Ryan; Ngee Derk Tiong; Bhaveet Radia; Lenka Janik Blaskova (Center for Educational Policy Studies Journal)
This paper advances our understanding of how schools can become change agents capable of transforming local practice to address the challenges arising from the Covid-19 pandemic. It presents a novel application of cultural-historical activity theory to reinterpret evidence on widespread learning loss and increasing educational inequities resulting from the pandemic, and to identify scalable transformative learning opportunities through reframing the crisis as a double stimulation. By reviewing evidence of the emerging educational landscape, we first develop a picture of the new ‘problem space’ upon which schools must act. We develop a problem space map to serve as the first stimulus to articulate local challenges. Integrating this problem space with research on professional change, we identify conceptual tools to capture learning gaps and implement pedagogic interventions at scale, in order to enhance schools’ agency in directly addressing the crisis. These tools can act as the second stimulus, enabling educators to address local challenges. We conclude by discussing the Covid-19 educational crisis as a unique stimulus for professional learning and outline the potential for durable shifts in educational thinking and practice beyond the pandemic. We argue that this unprecedented historic disruption can be harnessed as a transformative professional learning opportunity. In particular, we consider how research on professional change offers local, scalable interventions and tools that can support educators in preventing the new insights from ‘slipping away’ post-pandemic. Utilising the notions of boundaries and tool-mediated professional change, we examine the ways in which this disruption generates opportunities to envision alternative futures for equitable learning in school.